Analysis of element content in scalp hair of healthy people and breast-cancer patients with SEM/EDX method [2] - Kiliç, Eser; Öztürk, Sema; Demiroglu-Zergeroglu, Asuman; Yilmaz, Zeki; Yildiz, Oğuz Galip; Akkurt, Mehmet; Saraymen, Recep (My University, 2004)
[No abstract available]
Keywords: aluminum; barium ion; calcium ion; carbon; carcinogen; chloride ion; copper ion; element; indium; iron; lead; magnesium; magnesium ion; mercury; mitogenic agent; oxygen; potassium ion; rhenium; rubidium ion; silicon; sodium ion; strontium; zinc ion; breast cancer; cancer screening; chemical analysis; diagnostic test; hair analysis; human; letter; sampling; scalp hair; scanning electron microscopy; X ray microanalysis